On differential operators with singularity and conditions of discontinuity inside an interval - Amirov, R. Kh.; Yurko, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We investigate boundary-value problems for differential equations with singularity and discontinuity conditions inside an interval. We describe properties of the spectrum, prove a theorem on the completeness of eigenfunctions and associated functions, and study the inverse spectral problem.